Optimalisasi Penggunaan Media Sosial Untuk Dampak Positif di Kalangan Mahasiswa Teknik Informatika Universitas Ibnu Sina Batam - Ghea Paulina Suri; Aprizal Y; Firman Firman; Hanafi Hanafi; Hidayatul Ikhsan; Hilda Herasmus; Indra Sufian (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
This community service program aims to optimize social media use among students of the Faculty of Informatics Engineering at Ibn Sina University Batam. Through a series of Zoom meetings, students received training on prudent and productive use of social media, along with strategies for leveraging it in academic and professional contexts. The evaluation of the program indicates a significant improvement in participants' knowledge and skills, though there were some challenges in initial practical application. Discussion and Q&A sessions were highly beneficial, but there were suggestions to include more in-depth topics and practical sessions. Overall, the program has had a positive impact on preparing students to use social media effectively, with participants recommending it to their peers.